Projeto Educação e Agroecologia nas Escolas do Campo de Territórios da Reforma Agrária : os fazeres da Escola Filha da Luta Patativa do Assaré - Wanderley, Kamila Karine dos Santos (2025)
This study analyzes pedagogical practices considering the principles of Agroecology and Popular Education at the Filha da Luta Patativa do Assaré Rural School, located in the Santana da Cal Settlement, Canindé-CE. The research is linked to the Popular Education line of the Graduate Program in Education (PPGE) at the Federal University of Paraíba (UFPB). The research problem seeks to answer the following question: What role do Agroecology and Popular Education play in pedagogical practices in schools within Agrarian Reform territories? To address this question, the specific objectives are: I. Identify historical and theoretical aspects of agroecology in schools associated with the MST, analyzing its influences and challenges; II. Understand how MST schools have integrated Agroecology into Education, considering the principles of Popular Education; III. Explore the agroecological practices of the Filha da Luta Patativa do Assaré Rural School. This qualitative research follows the principles of Participatory Research (Brandão, 2006; Brandão & Borges, 2007; Melo, 2005). The study was conducted between 2021 and 2024, adopting a methodology based on the Systematization of Experiences (Holliday, 2012; Amâncio & Souza, 2022), Participant Observation (Silva, 2019; Minayo, 2001), and Semi-Structured Interviews, developed using the Oral History methodology (Pollak, 1992; Thompson, 1992). These instruments enabled the systematization of findings within the context of the experiences. The research involved eight educators, six of whom were directly engaged in the project’s actions at the school, the study's locus, and two in the project's Political-Pedagogical Coordination (CPP). The thesis we defend is that Agroecology, anchored in Popular Education, is more than a pedagogical proposal: it is a social practice, a science, and a political movement that transforms Rural Education. Based on the experience of the School linked to the MST, we analyze how agroecological knowledge is collectively built within the struggle for Agrarian Reform. The training process of the project highlighted that the integration between theory and critical practice emancipates subjects and strengthens the connection between Agroecology and basic education in Agrarian Reform territories. The results indicate that Agroecology emerged as a guiding thread, integrating local knowledge and promoting a critical and transformative pedagogical practice. Despite limitations in accessing internal dynamics and challenges in systematizing experiences, the study reinforces the relevance of Popular Education and Agroecology in emancipatory education within Agrarian Reform territories. Thus, this dissertation contributes to understanding this interrelationship, highlighting the potential of education as a path to environmental awareness.